Pengaruh Musik Klasik terhadap Nyeri Persalinan pada Ibu Primigravida Fase Aktif - Harahap, Novy Ramini; Rauda, Rauda; Sakinah Gurusinga, Devi Putri (Jurnal MID-Z (MIDWIFERI ZIGOT), 2025)
Classical music therapy can stimulate the release of endorphins which create a feeling of relaxation and calm. This occurs because the midbrain releases Gamma Amino Butyrate (GABA) through neurotransmitters which provide an analgesic effect, thereby reducing the perception of pain during labor. Based on WHO data (2023), the global maternal mortality rate (MMR) reached 305,000 per 100,000 live births, while in North Sumatra there were 131 cases (6.87%) recorded in 2022. This research aims to determine the effect of classical music therapy on labor pain of primigravid mothers in the first active phase at BPM Erlikasna. The research design used a quasi-experiment with a one group pre-test-post-test method and a total sampling of 10 respondents. Data analysis used the Paired Sample T-Test. The results showed that before therapy there were 2 mothers with mild pain, 6 with moderate pain, and 2 with severe pain. After therapy, mild pain increased to 6 people and moderate pain to 4 people. The statistical test results show a value of p = 0.010 (p < 0.05), which indicates that there is a significant influence of classical music therapy on reducing labor pain in primigravida mothers during the first active phase in BPM Erlikasna, Finish District, Langkat Regency.